Determinants of Repurchase Intention Based on Experience, Trust, and Customer Satisfaction in Ordering Ride-hailing Services on the Gojek Application (A Study on Students at UPN “Veteran” East Java) - Nindi Irmaya; Jojok Dwiridotjahjono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Customer Experience, Trust, and Customer Satisfaction on Repurchase Intention in ordering GoRide services on the Gojek application, focusing on students of UPN “Veteran” East Java. The method used in this study is quantitative with a multiple linear regression approach. Data were collected through questionnaires distributed to 100 respondents with a purposive sampling technique. The results showed that Customer Experience had a positive and significant effect on Repurchase Intention. However, Trust and Customer Satisfaction did not have a significant effect partially on Repurchase Intention. However, simultaneously, the three variables had a significant effect on customers' decisions to use GoRide services again.